2021
DOI: 10.1007/s40200-021-00820-4
|View full text |Cite
|
Sign up to set email alerts
|

Minocycline alleviates nociceptive response through modulating the expression of NR2B subunit of NMDA receptor in spinal cord of rat model of painful diabetic neuropathy

Abstract: Background It has been reported that neuropathic pain can be overcome by targeting the NR2B subunit of N-methyl-Daspartate receptors (NR2B). This study aimed to investigate the effects of minocycline on phosphorylated and total expression of NR2B in the spinal cord of rats with diabetic neuropathic pain. Methods A total of 32 Sprague-Dawley male rats were randomly assigned into four groups (n = 8); control healthy, control diabetic (PDN), and PDN rats that received 80 µg or 160 µg intrathecal minocycline respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Patients' reactions to various pharmacological and non-pharmacological treatments (in terms of type and dose) are extremely varied. A crucial component in this variance could be how the pain message is transformed in the CNS 46,47 . As it ascends from its entry port (the dorsal horn), travels through the CNS, and reaches the cerebral cortex, the pain signal can be amplified or diminished (the area crucial for consciousness).…”
Section: Mechanisms Of Pain Neuropathic Variationmentioning
confidence: 99%
“…Patients' reactions to various pharmacological and non-pharmacological treatments (in terms of type and dose) are extremely varied. A crucial component in this variance could be how the pain message is transformed in the CNS 46,47 . As it ascends from its entry port (the dorsal horn), travels through the CNS, and reaches the cerebral cortex, the pain signal can be amplified or diminished (the area crucial for consciousness).…”
Section: Mechanisms Of Pain Neuropathic Variationmentioning
confidence: 99%
“…Minocycline inhibits central [ 98 101 ] and peripheral [ 102 , 103 ] glial cell activity and attenuates the release of pro-inflammatory cytokines such as IL-1β [ 104 , 105 ] and TNF [ 106 ]. There is limited data suggesting that minocycline might also confer analgesia by binding to the NR2B subunit of N-methyl-D-aspartate (NMDA) receptors [ 107 ]. Because minocycline crosses the blood-brain barrier, recent focus has been on its potential neuroprotective effects [ 108 , 109 ], but clinical efficacy for this indication remains uncertain [ 110 ].…”
Section: Main Bodymentioning
confidence: 99%
“…Numerous murine studies have demonstrated analgesic benefit in a variety of mechanistic pain categories, including neuropathic pain ( e.g ., mechanical allodynia and hyperalgesia [ 105 , 111 , 112 ], chemotherapy-induced peripheral neuropathy [CIPN] [ 113 , 114 ], and painful diabetic neuropathy [ 107 , 115 117 ]), nociceptive pain [ 96 , 97 , 118 , 119 ] (including visceral pain [ 120 122 ]), and mixed pain conditions ( e.g ., endotoxin-induced hyperalgesia and arthralgia [ 123 ], and cancer-associated bone pain [ 124 , 125 ]). Minocycline potentially improves affective components of pain, such as depression, anxiety, and fear [ 126 128 ], and older studies suggested that minocycline might also prevent the development of opioid tolerance via glutaminergic or anti-microglial mechanisms [ 129 , 130 ].…”
Section: Main Bodymentioning
confidence: 99%